Several Subclasses of r-Fold Symmetric Bi-Univalent Functions possess Coefficient Bounds - Hameed, Mustafa I.; Shihab, Buthyna Najad (Iraqi Journal of Science, 2022)
In this paper we offer two new subclasses of an open unit disk of r-fold symmetric bi-univalent functions. The Taylor-Maclaurin coefficients have their coefficient bounds calculated. Furthermore, for functions in , we have solved Fekete- functional issues. For the applicable classes, there are also a few particular special motivator results.